2022
DOI: 10.1007/s10753-022-01734-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variants Show a Gradual Declining Pathogenicity and Pro-Inflammatory Cytokine Stimulation, an Increasing Antigenic and Anti-Inflammatory Cytokine Induction, and Rising Structural Protein Instability: A Minimal Number Genome-Based Approach

Abstract: Hyper-transmissibility with decreased disease severity is a typical characteristic of the SARS-CoV-2 Omicron variant. To understand this phenomenon, we used various bioinformatics approaches to analyze randomly selected genome sequences (one each) of the Gamma, Delta, and Omicron variants submitted to NCBI from December 15 to 31, 2021. We report that the pathogenicity of SARS-CoV-2 variants decreases in the order of Wuhan > Gamma > Delta > Omicron; however, the antigenic property follows the order of Omicron >… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 61 publications
5
10
0
Order By: Relevance
“…Performing analogous in silico modelling on other VoCs, including Alpha, Gamma, and Delta variant, showed a decrease in the number of dimerization modes after the Alpha variant, with 6, 7, 5, 4, and 3 modes of TLR4/MD2 dimerization for the wild-type, Alpha, Gamma, Delta, and Omicron VoCs, respectively (Figures for Alpha, Gamma, and Delta variants in Supplementary data, Tables S1-S3 and Figures S1-S3). These data correlate with data from recent studies, which indicate a narrowing cytokine pattern during evolution of the SARS-CoV-2 [82,83].…”
Section: In Silico Analyses Of Tlr4/md-2 Binding and Dimerization By ...supporting
confidence: 90%
See 2 more Smart Citations
“…Performing analogous in silico modelling on other VoCs, including Alpha, Gamma, and Delta variant, showed a decrease in the number of dimerization modes after the Alpha variant, with 6, 7, 5, 4, and 3 modes of TLR4/MD2 dimerization for the wild-type, Alpha, Gamma, Delta, and Omicron VoCs, respectively (Figures for Alpha, Gamma, and Delta variants in Supplementary data, Tables S1-S3 and Figures S1-S3). These data correlate with data from recent studies, which indicate a narrowing cytokine pattern during evolution of the SARS-CoV-2 [82,83].…”
Section: In Silico Analyses Of Tlr4/md-2 Binding and Dimerization By ...supporting
confidence: 90%
“…The study compared the cytokine profiles of patients with different variants of SARS-CoV-2 and showed that hypercytokinemia and cytokine storm become less threatening with the emergence of new mutations in the viral genome, being already visible with the Delta variant and most pronounced for the Omicron variant [82]. A similar tendency of decreasing pathogenicity has been shown by Barh et al showing decreasing pathogenicity (correlating with decreasing cytokine release) with virus evolution, with Wuhan strain > Gamma > Delta > Omicron [83].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These authors also reported that the so-called cytokine storm and the general "hypercytokinemia" exhibited a marked attenuation after emergence of the new Omicron variant. Interestingly, these findings were confirmed in a subsequent study published by Barh et al [41], who reported that pro-inflammatory cytokines production (especially interleukin 6) is decreased in patients infected with the Omicron compared to those infected by Delta variant. In keeping with these findings, Park et al studied nearly 30000 veterans with Alpha, Delta and Omicron infections [42] and observed that the risk of having enhanced levels of C Reactive protein was higher in those infected by Delta (Odds Ratio [OR], 2.30; 95%CI, 2.18-2.4) or Alpha (OR, 2.29; 95%CI, 2.14-2.45) compared to Omicron.…”
Section: Discussionsupporting
confidence: 59%
“…Well established knowledge since pioneering work of May & Andersen [32], and widely demonstrated along the COVID-19 pandemic, transmissibility is not related, or even is inversely related, to virulence. Contrasting 2003 SARS epidemic to the most recent SARS-CoV-2 pandemic, it is clear that a virulent variant/genotype will decrease its incidence in the host population, while those genotypes which are less virulent may evolve towards forms which are more transmissible, thus, becoming highly incident, even though more difficult to detect due to low hospitalization [33][34][35][36][37] Even though virulence of dengue is expected to be preserved along time due to the insect vector phase, especially considering vertical transmission [38], a newly arriving serotype must cause more severe disease but not further dissemination. On the contrary, the fast hospitalization removes a host to the transmission cycle.…”
Section: Discussionmentioning
confidence: 99%